Introduction - Colfer, C.J.P.; Yuliani, L. (2010)
This special section of Volume 41 of the Borneo Research Bulletin has been compiled in honor of Dr. Reed Lee Wadley, an anthropologist who conducted research for two decades in the Danau Sentarum area before dying prematurely in June 2008. We have assembled more recent research in the area, at the invitation of Dr. Cliff Sather and with the encouragement of Dr. George Appell. The compilation is multidisciplinary, bringing together researchers from the fields of anthropology, economics, botany, earth sciences, ecology, geology, geography, law and soil science. The authors also work in a range of research settings and include university professors, consultants, NGO personnel and people working in research organizations. We believe that Reed Wadley would have been particularly supportive of this diversity, given his own extraordinarily diverse interests and areas of expertise.